Pengaruh Price dan Product Quality Terhadap Costumer Loyalty Internet Indosat Ooredo di Sukabumi - Umban Adi Jaya; Santun Insan Bagja; Bambang Somantri (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2020)
This research is motivated by a decrease in the number of customers in the last 3 (three) years which indicates a decrease in customer loyalty to Indosat Ooredo. With the existing problems, this study aims to examine the effect of price and product quality on Indosat Ooredo's internet customer loyalty in Sukabumi. The research method used is quantitative descriptive, using a sample of 100 Indosat Ooredoo internet users in Sukabumi. The results of the study show that R square value is 67.1%, which indicates customer loyalty is determined positively and significantly by product quality and product quality with a regression equation Y = 4,709 + 0,100 X1 + 0,288 X2. Simultaneous analysis results show that price and product quality affect customer loyalty. The t test shows that there is no partial effect between the price of Indosat Ooredo Internet Loyalty Customers in Sukabumi. Partially there is a positive and significant effect between Product Quality on Indosat Ooredo's Internet Customer Loyalty in Sukabumi.